The Influence of Trust and Ease of Use on User Satisfaction and Loyalty of the Gojek Application : A Study of Passengers at Gubeng Station in Surabaya - Dian Fatimatuz Zuhro; Any Urwatul Wusko (Penerbit Jurnal Indonesia, 2025)
The development of digital technology has changed people's mobility patterns, including in the use of online transportation services such as Gojek. This study aims to analyze the influence of trust and ease of use on the satisfaction and loyalty of Gojek app users, with a case study of passengers at Gubeng Station in Surabaya. This study uses a quantitative approach with an explanatory research method, involving 110 active Gojek users selected through purposive sampling. Data were collected through a Likert scale questionnaire and analyzed using SmartPLS 4 to test validity, reliability, and relationships between variables. The results show that trust and ease of use have a positive and significant effect on user satisfaction, which is proven to significantly influence user loyalty, while the direct effect of trust and ease of use on loyalty is not significant. These findings confirm that satisfaction is an important mediator in shaping customer loyalty. Therefore, Gojek needs to improve service transparency, give users more control, and strengthen a consistent and personalized service experience. This study also recommends exploring other variables such as service quality, price, and promotions for further research.